Gender Harmony and Family Resilience on Online Motorcycle Drivers in Ponorogo Regency During the Covid-19 - Evi Muafiah; Ulin Nadya Rif'atur Rahmah; Neng Eri Sofiana; Maslathif Dwi Purnomo (Muwazah, 2022)
Online motorcycle drivers were one of the informal workers impacted by the Covid-19 for economic issues. The crisis effect was not only allied to physical, but also social and psychological aspects. Society was required to adapt and survive for facing unpredictable changes during this time. Any effort to overcome various problems in family life could not be separated from the agreement to divide several roles, following a gender harmony concept which encouraged the application of multiple parts and positions in family life with a balanced proportion based on each one’s interest to support mutual progress and realize gender equality and justice. This study was aimed to identify the implementation of a gender harmony approach for reinforcing online motorcycle drivers’ family resilience amid the Covid-19 pandemic era. Findings indicated that the drivers’ family resilience was strengthened by having double incomes due to providing more access for both husbands and wives to earn money. The value was also fortified by instilling several principles such as communication, commitment, and cooperation in both public and domestic works. However, one of the respondent’s families did not reflect a gender harmony relative because of having a double burden in the home that realized gender inequality and inequity.